2010
DOI: 10.1080/00221321003657445
|View full text |Cite
|
Sign up to set email alerts
|

Family Relationships and the Psychosocial Adjustment of School-Aged Children in Intact Families

Abstract: The authors investigated whether the quality of three family relationships (i.e., marital, parent-child, sibling) in intact families are associated with each other and with children's psychosocial adjustment. Data were collected by means of maternal and child reports (N = 88) using standardized instruments (i.e., Marital Satisfaction Scale, Strengths and Difficulties Questionnaire). The findings confirm associations between the marital and the parent-child relationship, and between the parent-child and the sib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
8

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 53 publications
1
19
0
8
Order By: Relevance
“…The results of our study are in line with studies that have shown how elevated levels of conflicted interactions and poor-quality family relations (degree of trust, warmth, fun, and togetherness) contribute to the development of depressive symptoms (35-38). The significance of both the relation with parents and family conflict resolution may be explained through the family system theory according to which different family subsystems (marital, parent-child, and sibling relationships) mutually influence each other (39). Emotions or behavior in a specific family subsystem may influence other subsystems within the family.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study are in line with studies that have shown how elevated levels of conflicted interactions and poor-quality family relations (degree of trust, warmth, fun, and togetherness) contribute to the development of depressive symptoms (35-38). The significance of both the relation with parents and family conflict resolution may be explained through the family system theory according to which different family subsystems (marital, parent-child, and sibling relationships) mutually influence each other (39). Emotions or behavior in a specific family subsystem may influence other subsystems within the family.…”
Section: Discussionmentioning
confidence: 99%
“…Among the few studies that have examined father-adolescent hostility and conflict, some studies have shown that father-adolescent hostility is uniquely associated with indicators of adolescent maladjustment, including internalizing and externalizing problems (El-Sheikh & Elmore-Staton, 2004), problem behaviors (Hakvoort, Bos, Van Balen, & Hermanns, 2010), and depressive symptoms (Pasch et al, 2006). Thus, these results suggest that father-adolescent hostility is important for adolescent well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the correlation between mother- and father adolescent hostility is high (i.e., r > .50) (e.g., Hakvoort et al, 2010). However, research also has shown that mother- and father-adolescent hostility are uniquely associated with some indicators of adolescent well-being (Adams & Laursen, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, all the subsystems in a family are connected and interlinked in such a way that any change in one produces changes elsewhere. This is evident in the available literature which advocates a strong link between the quality of family relationships and psychosocial adjustment of children [22][23][24]. Parent child relationship quality and connectedness affects psychosocial adjustment of children which in turn influences substance use in a child or an adolescent [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%